Reflection/Transmission Characteristics of a Discontinuous Galerkin Method for Maxwell's Equations in Dispersive Inhomogeneous Media (Journal of Computational Mathematics, 2018)
In this paper, we analyze the transmission and reflection properties of a high order discontinuous Galerkin method for dispersive Maxwell's equations, originally proposed by Lu et al. [J. Comput. Phys. 200 (2004), pp. 549-580]. We study the reflection and transmission properties of the numerical method for up to second-order polynomial elements for one- and two-dimensional Maxwell's equations with rectangular meshes. High order accuracy has been shown for reflection and transmission coefficients near material interfaces.